Wewenang Kejaksaan Tinggi Bali Dalam Litigasi Perdata: Perspektif Hukum dan Implementasinya - Permana, I Made Adi Ananda (STIE Jambatan Bulan, 2026)
This study examines the authority of the Bali High Prosecutor’s Office in civil litigation, focusing on its legal basis, implementation, and the challenges faced in practice. As the state attorney, the Bali High Prosecutor’s Office plays a crucial role in safeguarding the state’s legal interests, including filing lawsuits, providing defense, and resolving disputes related to state assets, government contracts, and public interests. The research employs a descriptive qualitative method through observation, interviews, and document analysis conducted during field practice at the Bali High Prosecutor’s Office. The findings reveal that the institution holds broad authority but encounters obstacles such as limited human resources and low public awareness of its role in civil litigation